Agenesis of Medial Patellofemoral Ligament (MPFL) with Habitual Patellar Dislocation in Adolescent Woman with Cerebral Palsy – A Case Report - Nurul Hidayah; Felix Giovanni Hartono; Bramta Putra Manyakori; Agus Sari Budaya (Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: The current treatment for habitual dislocation and nonoperative treatment failure is surgical therapy. Therefore, this study describes chronic patella dislocation's comprehensive evaluation and management in an adolescent woman with cerebral palsy (CP).Case Report: A 15 years old female patient has suffered knee pain for almost three years. Furthermore, the physical examination revealed positive adam's forward bending test and left knee cap dislocation with positive patellar J-sign at 90°. Radiologic examination of the vertebrae and left knee shows scoliosis left thoracolumbar curved with 43 cobb angle and patellar shift. The patient was then diagnosed with habitual patellar dislocation, spastic diplegia type of CP, and neuromuscular scoliosis, consulted to the pediatric department, and then planned for medial patellofemoral ligament (MPFL) reconstruction. During the surgical examination, we discovered the MPFL Agenesis. Finally, lateral release and plication of the medial retinaculum were selected for surgery and planned to receive a Boston brace for scoliosis. After six weeks of follow up, the patient shows a reduction in pain.Discussion: Lateral release and MPFL reconstruction for patellar stabilization generate better results. However, in this case, the absence of the medial patellar facet and the medial femoral condyle enhances Lateral release and plication of the medial retinaculum more preferable to fixate the left patella and improve functional limitation.Conclusion: Comprehensive and immediate treatment for a patient with habitual patella dislocation and other predisposition diseases increases the chances of success.